The AI Design Revolution’s Impact: Transforming Consumers To Creators - Londhe, Rechab; Soni, Gunja; Mirza, Imran (Journal of Neonatal Surgery, 2025)
The revolutionary impact of artificial intelligence (AI) on the design field is examined in this study, with a particular emphasis on how AI helps turn customers into active designers. Trends analysis is a method frequently used in design to analyse current and possible future trends. [7] With the development of AI technology, customers are no longer only beneficiaries of things that are made for them; rather, they are now actively involved in the design process. The development of AI paved the path for intelligent interior design solutions and, in the end, began to pose a challenge to interior designers by enabling customers to use new materials with ease when applied correctly. The aforementioned advancements in technology, such as augmented reality and artificial intelligence, social media, user-friendly design software, interior planning apps, and online material information, are increasing the potential of the final product and streamlining the process from point Business (B) to Consumers (C). Thus, in this day and age where technology manages and gives direct accessibility to the user, the idea of Do It Yourself (DIY) emerges. In other words, by creating items for their homes on their own, buyers avoid hiring interior designers for interior design work. This research seeks to shed light on how the AI design revolution is changing the dynamic between creators and customers in the modern world by examining the potential, problems, and ethical issues surrounding this phenomenon.